Agreement of anterior ocular biometric measurements with a new optical biometer and a Scheimpflug tomographer. Issue 5 (May 2016) - McAlinden, Colm; Bao, Fangjun; Guo, Yan; Yu, Xinxin; Lu, Weicong; Chen, Hao; Wang, Qinmei; Huang, Jinhai
Abstract : Purpose : To evaluate the agreement between a new optical biometer (AL‐Scan) and an anterior‐segment Scheimpflug tomographer (Pentacam HR). Setting : Eye Hospital of Wenzhou Medical University, Zhejiang, China. Design : Prospective randomized comparative case series. Methods : Three consecutive scans of the right eye of each subject were obtained using each device in a random order. The following common parameters were recorded: central corneal thickness (CCT), anterior chamber depth (ACD), aqueous depth, and keratometry (K) readings (steep, flat, and mean). Bland‐Altman limits of agreement (LoA) were calculated for the common device parameters. Results : The study comprised 121 healthy subjects (57 men, 64 women) with a mean age of 25.41 years ± 6.86 (SD) (range 18 to 54 years). The mean difference in CCT was 1.61 μm with LoA of −6.29 to 9.52 μm. The mean difference in the aqueous depth and ACD was 0.02 mm with LoA of −0.10 to 0.14 mm and −0.09 to 0.14 mm, respectively. For the 2.4 mm K readings from the new biometer versus the standard K readings from the Scheimpflug tomographer, the mean difference for flat K, steep K, and mean K was 0.10 diopter (D), 0.05 D, and 0.08 D, respectively. The LoA were −0.17 to 0.38 D, −0.29 to 0.39 D, and −0.19 to 0.34 D, respectively. The CCT, ACD, and all K readings were assessed to be clinically interchangeable. Conclusion : There was good agreement between the 2 devices for CCT, ACD, aqueous depth, and K readings. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.